Faktor Determinan Keberhasilan Pemberian ASI Eksklusif pada Bayi Usia 7–12 Bulan - Sitti Fatimah; Muhammad Khidri Alwi; Tutik Agustini; Idelriani (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2026)
Exclusive breast milk is breast milk that must be given or breastfed to a newborn baby until the baby is 6 months old, without giving anything additional to the baby. Where while giving exclusive breast milk, the mother does not need to give anything additional to her baby, whether water, fruit juice or formula milk. The research design in this study is a cross-sectional research study. Sampling used total sampling with a total of 58 mothers as respondents, data collection used a questionnaire. The results of this study showed husband support factors (p=0.005), breast milk production (p=0.008), maternal psychology (p=0.006). The conclusion of this research is It is hoped that husbands, family and friends will support mothers in providing exclusive breastfeeding, such as listening to a mother's stories and complaints while breastfeeding to help reduce the uncomfortable burden and worry during breastfeeding.